EFFECTS OF DIETARY NUTRIENT CONCENTRATIONS ON PERFORMANCE, CARCASS TRAITS AND MEAT QUALITY OF ORGANICALLY REARED BARRED PLYMOUTH ROCK BREED - Ioan Custura; Minodora Tudorache; Anca Gheorghe; Nicoleta Aurelia Lefter; Mihaela Habeanu; Gratziela Victoria Bahaciu; Andra Dorina Suler; Ion Raducuta (Journal of Animal and Plant Sciences, 2024)
The high demand for organic agricultural food requests increased concern for organically produced poultry products' production, management and marketing. The study aimed to assess the performance, carcass traits, chemical and amino acids (AA) composition of breast and thigh meat organically reared Barred Plymouth Rock (BPR) chicks fed different nutrient concentrations. 240 one-day-old BPR chicks were allocated into three treatments (8 replicates of 10 chicks each) and used in an 84 d feeding trial according to organic meat technology. Dietary treatments consisted of a basal isoenergetic and isoproteic organic diet as a control (T0), isoenergetic and low-crude protein (CP) level organic diet (T1; 1% CP lower) and isoproteic and low-metabolizable energy (ME) level organic diet (T2; 220 kcal/kg ME lower). Results showed that dietary treatments did not influence the overall period body weight and weight gain of BPR chicks, but feed intake and FCR were significantly increased in experimental (T1 and T2) diets than in control. There were no effects of dietary treatments on carcass traits and digestive organs. Proximate composition (dry matter, fat, protein, ash) and energy value of meat were not altered by treatments, except the protein content of thigh muscle significantly decreased in T1 compared to the other treatments. Certain individual AA, which included phenylalanine in breast muscle, as well as lysine and phenylalanine in the thigh muscle, decreased by fed T1 diet, leading to a significant decrease in both breast and thigh muscles of total AA (TAA) and essential AA (EAA) in T1 than the other treatments. The non-essential AA (NEAA) and the ratios of EAA/TAA or EAA/NEAA did not differ among treatments. Our results show that irrespective of dietary treatments or muscle type, the meat of BPR chicks has a balanced AA profile with more than 40% EAA/TAA ratio and more than 60% EAA/NEAA ratio. In conclusion, these findings indicate that fed low-energy diet (T2) in BPR chicks represents an alternative with no adverse effect on productive performance, carcass traits, and meat protein quality.
Keywords: organic; carcass; growth performance; nutrient concentrations; meat composition.